Deterioro de la propiedad planta y equipo en el Gobierno Autónomo Descentralizado Municipal del cantón Vinces en el periodo comprendido desde el 1 de enero al 31 de diciembre del 2019 - Neira Zuñiga, Maverick Jackson (2021)
The present case study has as its theme the Deterioration of the Property Plant and Equipment in the Municipal Decentralized Autonomous Government of the Canton Vinces in the period from January 1 to December 31, 2019, its purpose is to examine whether the Municipal Decentralized Autonomous Government of the Canton Vinces maintains irregularities in the depreciation of the Property Plant and Equipment, this considering that being a public sector entity must be governed by the regulations of the Comptroller General of the State, such as the General Manual of Administration and Control of Fixed Assets of the Public Sector, the Internal Control Standards of the Comptroller General of the State and the General Regulations for administration, Use, Management and Control of Public Sector Assets and Stocks. To carry out this case study, the deductive method was used, descriptive considering that it is based on the information obtained through the interview technique which was carried out when representing the department of goods and warehouse, while the subline is established as Audit and Control, the same that allows us to analyze the accounting treatment that the GAD gives to the goods that are considered Property Plant and Equipment, highlighting in this study the deterioration and the low that is given to them.